2019
DOI: 10.1088/0253-6102/71/8/939
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characterization of Couplings in a Mixed Optomechanical Model*

Abstract: We study the spectrum of single-photon emission and scattering in a mixed optomechanical model which consists of both linear and quadratic optomechanical interactions. The spectra are calculated based on the exact long-time solutions of the single-photon emission and scattering processes in this system. We find that there exist some phonon sideband peaks in the spectra and there are some sub peaks around the phonon sideband peaks under proper parameter conditions. The correspondence between the spectral featur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Let us denote |m a (m = 0, 1, 2, ...) and | j b ( j = 0, 1, 2, ...) as the number states of the cavity field and the mechanical oscillation, respectively. Then the eigen-equation of the Hamiltonian H mop can be derived as [53]…”
Section: Physical System and Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…Let us denote |m a (m = 0, 1, 2, ...) and | j b ( j = 0, 1, 2, ...) as the number states of the cavity field and the mechanical oscillation, respectively. Then the eigen-equation of the Hamiltonian H mop can be derived as [53]…”
Section: Physical System and Hamiltonianmentioning
confidence: 99%
“…In the mixed cavity optomechanical system, the two optomechanical coupling strengths g 1 and g 2 take important roles in the spectrum features. It has been found that, in the single-photon scattering case, the single-photon strong-coupling condition g 1 > γ c is a necessary parameter condition for the exhibition of these phonon sideband peaks (the distance between neighboring phonon sideband peaks is ω M ) [53]. In addition, when g 2 /ω M ≪ 1, the parameter condition 2g 2 > γ c is the necessary condition for observation of subpeaks in each phonon sideband.…”
Section: Two-photon Scattering Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies in cavity optomechanics are focused on either the first-order or quadratic optomechanical systems. However, the mixed cavity optomechanical model [51][52][53][54][55][56][57][58] with both the first-order and quadratic optomechanical couplings is a more basic model, which has attracted much recent attention from the community of optomechanics. There have been lots of works about the mixed cavity optomechanical model, including squeezing and cooling of mechanical mode [52], harmonic generation of self-sustained oscillations [53], quantum nondemolition measurements of phonons [54], optomechanically induced transparency [55], conditional preparation of nonclassical states [56], spectrum of single-photon emission and scattering [57], and detection of weak forces [58].…”
Section: Introductionmentioning
confidence: 99%
“…) [44][45][46][47][48][49]. Here g 1 and g 2 refer to the respective coupling strength between the optical mode and the mechanical mode.…”
mentioning
confidence: 99%